Critical pedagogy for food systems transformation: Identifying and addressing social-justice problems in food systems and society - Allen, Patricia; Gillon, Sean (Frontiers in Sustainable Food Systems, 2022)
Current crises in the food system have amplified and illuminated the need for urgent social change to increase equity and survivability. Global crises such as climate change, environmental degradation, and pandemics increasingly disrupt everyday lives and limit possibilities in the food system. However, the prevalence of these crises has not yet engendered commensurate rethinking on how to address these increasingly evident and desperate social problems. While food and food systems are at the core of survival, food systems issues are deeply intertwined with and inextricable from the structures and operating principles of society itself. Effective and equitable change requires new ways of thinking, ways that are different than those that led to the problems in the first place. This requires identifying, conceptualizing, and addressing social problems through critical inquiry that places social justice at the center in order to render visible and explicit the social injustices in problem causes and consequences, as well as transformative pathways toward social justice. One of the most important domains for this work is that of higher education, an arena in which crucial conceptual thinking can be supported. In this brief article we review why critical pedagogy should be a priority in higher education; discuss critical pedagogy for food systems equity; and illustrate how we apply critical pedagogy in the Food Systems and Society online Master of Science program at Oregon Health & Science University.